Protection of National Interests in International Business Agreements: Legal Challenges and Strategies in the Era of Digital Globalization - Yoan Yoan; Siandi Siandi; David David (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
The globalization of the economy and the development of digital technology have increased the intensity of cross-country business relations, manifested through various international business agreements. On one hand, international agreements provide opportunities for the growth of investment, trade, and technology transfer. On the other hand, there is a potential for national interests to be eroded if a country is unable to optimize the available legal instruments. This study aims to analyze the forms of protection of national interests in international business agreements as well as the legal strategies that Indonesia can implement in facing the development of the global economy. The research method used is normative legal research with statutory, conceptual, and comparative approaches. The research results indicate that the protection of national interests can be carried out through the strengthening of investment protection clauses, regulation of technology transfer, protection of natural resources, sovereignty over digital data, as well as the application of the principle of balance in international negotiations. The state needs to ensure that every international business agreement not only provides economic benefits but also guarantees the sustainability of national development.